Mesoporous Gold Nanospheres Confined Platinum Nanoclusters as Robust ROS and Oxygen Nanogenerators for NIR‐II Hyperthermia Cancer Therapy - Fei Cun; Jie Chen; Hanxue Li; Yufang Kou; Meiyan Wang; Xiaomin Li; Hui Chen; Jilie Kong (Advanced Science)
Abstract While massive studies are focused on platinum (Pt)‐based nanozyme for antitumor therapies, their therapeutic efficiency is deficient due to the weak catalytic activity in the highly complex tumor microenvironment. Herein, mesoporous gold nanospheres confined platinum nanoclusters (MGNSs@Pt) as robust hydroxyl radical and oxygen nanogenerators are achieved for multimodal therapies. Benefiting from the confinement effect of the mesopores in the MGNSs, the Pt nanoclusters (Pt NCs) demonstrate enhanced stability and catalytic activity, with a catalytic constant (Kcat) of 1.42 × 106 s−1, which is 2 and 5 orders magnitude higher than Kcat values of Pt‐decorated non‐porous gold nanoparticles and pure Pt NCs respectively. Density functional theory (DFT) calculations reveal the proper interaction of intermediates contributes to the ultra‐high catalytic activity of MGNSs@Pt. Meanwhile, owing to the local surface plasmon resonance (LSPR) effect in the second near‐infrared (NIR‐II) bio‐window of MGNSs, the nanozymes exhibited high photothermal conversion efficiency up to 43.4%, which enhanced the nanocatalytic damage on cancer cells. This process can induce robust oxidative stress and oxygenation within the tumor, thereby activating the apoptosis pathway for tumor eradication by mitochondrial dysfunction, cell membrane disruption, HIF‐1α downregulation as well as caspase 3 activation, which pave the way for multimodal and effective cancer treatment.